TOXICITY STUDIES OF PHOTO-FILM WASTES - Krishnamoorthi, K P; Deshpande, W M; Mohanrao, G J (Indian Journal of Fisheries, 2011)
The photo-film industry discharges three types of wastes, all of which are toxic tofish to some extent. The effluents in descending order of toxicity are the laboratoryeffluent, the emulsion wash water, and the white water, with their respective 48 hr TLmconcentrations at 1, 5 and 10 per cent. A mixture of the wastes composited on the basisof their flows had a 48 hr TLm of 5 per cent.Toxicity of the emulsion wash water was primarily due to the undissociatedammonia. Laboratory effluent toxicity was primarily due to hydroquinone and metolwhich showed synergistic effects. Thiosulphate and carbonate and to a much smallerextent sulphate had antagonistic effects on the toxicity of hydroquinone and meto!.Coagulation with aluminium sulphate and settling reduced tlie toxicity of the wastesconsiderably.